Molecular identification of Trichogramma species parasitizing Ostrinia nubilalis in corn and pepper in south–east border of Europe. Issue 4 (24th September 2021) - Ivezić, Aleksandar; Rugman-Jones, Paul; Malausa, Thibaut; Ris, Nicolas; Ignjatović-Ćupina, Aleksandra
Abstract: The current study extends the faunistic survey of Trichogramma species parasitizing ECB to all agricultural growing regions in Serbia. Specimens of Trichogramma were reared from parasitized egg masses of ECB collected from field-grown corn and pepper crops. The number of egg masses parasitized varied by location. Using sequences of mitochondrial cytochrome oxidase I (COI) gene, we examined intra and interspecific variation in Trichogramma parasitizing the ECB egg masses. Seventy specimens were successfully sequenced of which, 65 were identified as T. brassicae . The remaining five were identified as T. evanescens, and this second species was only collected from pepper.